Dose-Dependent Effects of Cannabis Edibles on Simulated Driving Performance - Bernard Le Foll; Justin Matheson; Paulina Antwi; Madison Wright; Adam Zaweel; Omer S. M. Hasan; Stefan Kloiber; Ahmed N. Hassan; Beth Sproule; Christine M. Wickens; Patricia Di Ciano; Bruna Brands (JAMA Network Open, 2026)
Importance Use of cannabis edibles is increasing, yet little is known about the impact of edibles on driving, which is particularly important in the context of per se thresholds (commonly 2 or 5 ng/mL) used to enforce cannabis-impaired driving laws. Objective To determine whether driving simulator performance is dose-dependently impaired by commercially available edible cannabis. Design, Setting, and Participants This randomized, double-blind, placebo-controlled, crossover clinical trial was completed at a single-site tertiary care academic hospital in Toronto, Ontario, Canada, between September 2024 and April 2025. Participants were healthy adults aged 19 to 45 years endorsing at least weekly cannabis use and monthly use of cannabis edibles. Interventions Edible (oral) delta-9-tetrahydrocannabinol (THC) was administered to all participants in soft-chew gummies, 0 or 2 mg each, to achieve doses of 0, 2, 10, and 20 mg. Main Outcomes and Measures Standard deviation of lateral position (SDLP) in simulated driving scenarios at 2 and 5 hours after THC exposure was the primary outcome (reported as difference in means [95% CIs]) assessed in the intention-to-treat population. Secondary outcomes included driving simulator standard deviation of speed (SDS) and reaction time (RT), self-reported driving willingness and perceived ability, and whole-blood THC and metabolite levels. Results Of 85 potential participants, 52 were enrolled as eligible, 10 withdrew before receiving a dose of THC, and 2 were removed from the analysis. Thus, 40 participants (20 [50.0%] female and 20 [50.0%] male) were included in the analysis (mean [SD] age, 30.4 [6.9] years). Relative to placebo, SDLP was significantly increased at 20 mg (3.3 [95% CI, 2.4 to 4.3] cm; P < .001) and 10 mg (2.0 [95% CI, 1.0 to 2.9] cm; P < .001), but not 2 mg (0.7 [95% CI, −0.3 to 1.6] cm; P = .16). The secondary driving measures RT and SDS were also negatively influenced by THC exposure. For example, compared with placebo, RT was significantly higher at 20 mg (difference in means, 0.034 [95% CI, 0.018 to 0.050] s; P < .001) and SDS was significantly increased at 20 mg (difference in means, 0.469 [95% CI, 0.154 to 0.784] km/h; P = .004). Self-reported driving measures were dose-dependently decreased by THC dose. For example, compared with placebo, willingness to drive was significantly decreased at 20 mg (difference in means, −2.113 [95% CI, 1.166-1.821]; P < .001), as was participant-perceived driving ability (difference in means, −1.694 [95% CI, 1.422-1.966] ; P < .001). Whole-blood THC concentrations (peaks of 3.4 and 1.6 ng/mL at 20 and 10 mg, respectively) were near or below common per se thresholds for driving. Conclusions and Relevance In this crossover randomized clinical trial of driving performance after exposure to THC edibles, THC dose-dependently impaired simulated driving performance at blood THC concentrations below per se thresholds commonly used for roadside enforcement. Trial Registration ClinicalTrials.gov Identifier: NCT06595576